2015
DOI: 10.1097/rli.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of the Prostate

Abstract: Selective-excitation accelerated reduced-FOV DW images (sTX-DWI) of the prostate can be acquired more than 5 times faster than rs-DWI with comparable image quality, at the expense of significantly increased geometric distortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…This difference was especially pronounced for susceptibility artifacts, most likely due to remaining air in the ER coil balloon causing inhomogeneities of the static magnetic field [30] and possibly the ER conducting wire loop itself. Moreover, incorrect placement and rotation of the ER coil itself may deform and/or displace the prostate and additionally lead to susceptibility artifacts in the posterior aspect of the gland [28,31]. These artifacts together with the higher SNR achieved in DWI sequences with the PPA coil-which was most likely the result of the higher number of averages chosen for this sequence-may have rendered the advantage of a higher resolution achieved by the ER coil void and most likely lead to the fact that on a side-by-side comparison both readers preferred PPA coil over ER coil image sets in more than half of the cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This difference was especially pronounced for susceptibility artifacts, most likely due to remaining air in the ER coil balloon causing inhomogeneities of the static magnetic field [30] and possibly the ER conducting wire loop itself. Moreover, incorrect placement and rotation of the ER coil itself may deform and/or displace the prostate and additionally lead to susceptibility artifacts in the posterior aspect of the gland [28,31]. These artifacts together with the higher SNR achieved in DWI sequences with the PPA coil-which was most likely the result of the higher number of averages chosen for this sequence-may have rendered the advantage of a higher resolution achieved by the ER coil void and most likely lead to the fact that on a side-by-side comparison both readers preferred PPA coil over ER coil image sets in more than half of the cases.…”
Section: Discussionmentioning
confidence: 98%
“…Functional imaging techniques, such as DWI, have become an integral part of mpMRI of the prostate [3,28] and comparative studies regarding the image quality of DWI between PPA coil and ER coil acquisition in the same patient remain sparse. A recent study has demonstrated a benefit of the use of an ER coil in detecting prostate cancer as compared to use of a PPA coil [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, for functional MR sequences (e.g. diffusion weighted imaging) the magnitude of distortion is much higher and requires dedicated study to investigate its optimal use in radiotherapy planning context [16] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…15 Due to briefer echo-trains and shorter echo-spacing, in comparison to conventional ss-DTI sequences, rs-DTI is capable of achieving a higher image resolution, an increased signal-to-noise-ratio (SNR) and a reduction of susceptibility-based artifacts. New rs-DTI has been applied previously in pelvic imaging, 18 prostate imaging, 19 cerebral imaging, 20,21 and lumbar nerve root imaging. 22 A direct comparison of ss-DTI and rs-DTI techniques for DTI of the brachial plexus is desirable before implementation in clinical routine and has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%